Can cancer registries show whether treatment is contributing to survival increases for melanoma of the skin at a population level?. Issue 1 (23rd September 2013) - Shahnam, Adel; Roder, David M.; Tracey, Elizabeth A.; Neuhaus, Susan J.; Brown, Michael P.; Sorich, Michael J.
Abstract Rationale, aims and objectives It is uncertain whether survival increases from melanoma recorded by some population registries include a treatment effect. The US Surveillance, Epidemiology and End Results (SEER) programme has good data quality control, large numbers of cases enabling high statistical precision and summary stage plus thickness, which we consider to be a best‐case population registry scenario to investigate potential for a treatment effect. We have investigated SEER data to indicate whether survivals increases are fully attributable to earlier diagnosis and other non‐treatment factors. Methods Through relative survival regression, the effects of diagnostic period on 5‐year excess mortality were investigated, adjusting for socio‐demographic factors, lesion sub‐site, histology, thickness and stage at diagnosis in 1990–2009 (n = 99 690 cases). Results The reduction in excess mortality (95% confidence interval) between 1990–1999 and 2000–2009 was 31 (20–41)% for localised melanoma, 18 (12–22)% for regional melanoma and 3 (–5–10)% for melanomas with distant spread. Younger age was predictive of a greater percentage reduction. Treatment benefits are inferred from the higher survivals in 2000–2009 but uncertainty remains due to incomplete data to adjust for non‐treatment factors and a lack of treatment data. Conclusions Registries should use new information systems to collect more complete data on stage, other prognostic indicators, co‐morbidities and treatment, to provide more definitive and detailed information on population effects of cancer control.